Konseling Pasca Nikah untuk Mengatasi Konflik Pasangan Usia Lima Tahun Pertama Pernikahan di GBI Musi Palem Indah Palembang - Tiara Greey Yani; Guntur Hari Mukti; Josep Tatang (JUITAK: Jurnal Ilmiah Teologi dan Pendidikan Kristen, 2025)
This study aims to analyze the role of post-marital counseling as a pastoral strategy in addressing marital conflicts during the first five years of marriage among congregants of the Bethel Church of Indonesia (Gereja Bethel Indonesia) Musi Palem Indah, Palembang. The first five years of marriage represent a critical period prone to various issues, such as personality differences, poor communication patterns, financial problems, spiritual crises, and the influence of secular culture. Although the church has implemented a premarital counseling program, data indicate instances of divorce among young married couples due to a lack of continuous guidance. This research employs a qualitative descriptive method using observation, semi-structured interviews, and questionnaires distributed to 25 couples who were married between 2020 and 2025. Data analysis was conducted through the stages of reduction, data presentation, and conclusion drawing, validated through source triangulation. The findings reveal that the majority of respondents (70–80%) acknowledged that post-marital counseling plays a significant role in resolving household conflicts, fostering healthy communication, and strengthening family spirituality. The key finding of this study is the effectiveness of the MUSI-based pastoral counseling model (Problem, Effort, Goal, Intervention), which is systematic, contextual, and spiritually integrative according to the needs of the local congregation. The study recommends that the church develop post-marital counseling programs as an integral part of pastoral family ministry in a preventive, structured, and continuous manner to strengthen Christian family resilience from the early stages of marriage.